Evaluación de riesgos laborales en altura, en los trabajadores en la empresa Quevedo cable televisión Q.V. cable S.A. - Mayorga Andriance, Diego Alfonso (2022)
Quevedo Cable Television Q.V. Cable S.A is a company dedicated to the transmission of sound, images and data by fiber optic cable, which carries out work at heights in its aerial fiber laying, supported in a reel where the post-to-pole process begins with the role assigned to each worker. The following research project had the objective of analyzing occupational safety in work at heights and its impact on health, focused on the risks of its workers, research methods such as observation during the laying and installation of the fiber were used. , the inductive method was useful for the realization of the conclusions, the analytical method in the description of the steps that are followed during the work, in turn the IPERC risk assessment matrix where the types and magnitude of the risks were classified, the survey to find out the situation and state of the staff regarding their knowledge of the stairs that are their daily tools and a check list, which allowed a better analysis of the risks to reach the conclusions that is the reduction of incidents or accidents at work for the benefit of the workers and the contribution of both national and international security protocols and laws, this research project was carried out carried out through the collection of both manual and written information, the diagnosis of the current situation of the place and its individual protection equipment and safety tools in their workplaces was carried out, projecting a fall prevention program. Key Words: IPERC, Prevention Programs, Transmission, Risks, Falls.